2021
DOI: 10.2139/ssrn.3834416
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Global Economic Uncertainty: Implications for the Euro Area

Abstract: This paper should not be reported as representing the views of the European Central Bank (ECB). The views expressed are those of the authors and do not necessarily reflect those of the ECB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Pekanov and Schiman (2020) analyze uncertainty in the euro area following the very first wave of COVID-19, by using market volatility (EAVSTOXX). 6 The authors find that, after an initial spike, uncertainty (measured by EAVSTOXX) levelled off more quickly than in the case of the GFC and cause a small macroeconomic damage. 7…”
Section: Bobasu Et Al (mentioning
confidence: 99%
See 1 more Smart Citation
“…Pekanov and Schiman (2020) analyze uncertainty in the euro area following the very first wave of COVID-19, by using market volatility (EAVSTOXX). 6 The authors find that, after an initial spike, uncertainty (measured by EAVSTOXX) levelled off more quickly than in the case of the GFC and cause a small macroeconomic damage. 7…”
Section: Bobasu Et Al (mentioning
confidence: 99%
“…The uncertainty measures considered inBaker et al (2020) are: stock market volatility, newspaperbased economic uncertainty, and subjective uncertainty in business expectation surveys6 The EPU, Twitter-based Economic Uncertainty Index and business expectations are also described, albeit not used in the VAR application.7 They use the EAVSTOXX, as preferred measure, in a VAR together with the euro area unemployment rate, the Euro OverNight Index Average (EONIA) and the year-on-year change of the Harmonised Index of Consumer Prices (HICP). The data for the applications are from January 1999 to August 2020.8©International Monetary Fund.…”
mentioning
confidence: 99%
“…In part because investment is more import intensive than other components of demand, weakening investment growth contributed to the slowdown in trade growth prior to the pandemic (figures 3.9.A and 3.9.B; Bobasu et al 2020;IMF 2016;World Bank 2021b). The commodity importers, in part because the improvement was less pronounced than the deterioration experienced by commodity exporters.…”
Section: Slower Trade Growthmentioning
confidence: 99%
“…For example, a terrorist attack in one country may discourage foreign investment, or a regional multiplier could enable the loss of economic activity in the nation targeted by terrorism to spread throughout the region (see, for instance, Murdoch and Sandler, 2004;or De Groot, 2010). Bobasu (2023) demonstrated that a rise in uncertainty of the eurozone's partners has the potential to affect the euro area economy to a significant degree. Furthermore, the rapid dissemination of information and the pervasive influence of globalization mechanisms ensure that events within one geographical region swiftly gain notoriety in other parts of the world (Balli et al, 2022;Monteiro et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%